Notes on the tragic experience of the phrase in Lacoue-Labarthe - Arias, Pablo (Re-presentaciones: Periodismo, comunicación y sociedad, 2023)
This paper aims to give an account of the main aspects that motivated Lacoue-Labarthe to think about tragedy, in order to relate them to the experience he called: phrase. To this end, the consideration of tragedy as mimesis is highlighted, in contrast to the cathartic reading that tradition has made of it. This problematic is related to Hölderlin’s work of translation and dramaturgy, which allows the thinker of "Typographie" to rethink the very experience of thought in its differential consideration.